Effect of statins on arterial wall inflammation as assessed by 18F-FDG PET CT: an updated systematic review and meta-analysis - Tannaz Jamialahmadi; Željko Reiner; Luis E. Simental-Mendia; Wael Almahmeed; Sercan Karav; Ali H. Eid; Francesco Giammarile; Amirhossein Sahebkar (Journal of Inflammation, 2024)
Abstract Background Pathogenesis of atherosclerosis is largely mediated by inflammatory process. Statins are lipid-lowering drugs which also have anti-inflammatory effects. 18 fluorine radiolabeled fluorodeoxyglucose (18 F-FDG) positron emission tomography-computed tomography (PET-CT) is considered to be a good indicator of arterial wall inflammation. Therefore, in this meta-analysis the role of statins on inflammatory process in the artery wall was evaluated using this method since its actual validity for this purpose is not yet well established. Methods PubMed, Scopus, Web of Science, ClinicalTrials.gov, and Google Scholar databases were searched using MESH terms and keywords. Funnel plot, Begg’s rank correlation, and Egger’s weighted regression tests evaluated publication bias in the meta-analysis. In cases where funnel plot asymmetry was observed, the “trim and fill” method was used to check the input of potentially missing studies. Results Findings of 10 clinical trials involving 373 subjects showed a remarkable reduction of arterial wall 18 F-FDG uptake according to target-to-background ratio (TBR) index after treatment with statins. Subgroup analysis showed a significant decrease in TBR with high-intensity and non-significant reduction of TBR with low-to-moderate-intensity statin therapy. Conclusion Treatment with statins suppressed arterial wall inflammation as shown by using 18 F-FDG PET-CT.